Systematics of Plankton Diversity in Thol Bird Sanctuary, Inland Wetlands, Gujarat - Karia, Jessica P.; Vachhrajani, Kauresh D.; Pandya, Pranav (Indian Forester, 2013)
Thol Bird Sanctuary in Kaditaluka (Mehsana district) of North Gujarat is among eighth national wetland sites in India which has been identified and declared for conservation. Plankton samples collected using 20 nm mesh size nylon plankton net had presence of total 14 phytoplankton and 22 zooplankton taxa identified from six sampling locations. Phytoplankton diversity showed that the Aphanocapsa sp. (fam:Cynophyceae) and Ankistrodesmus sp. (fam: Chlorophyceae) were dominating genera. Among zooplankton Arthropoda group had maximum members in all the sites followed by rotifers, protozoans and nematods. These studies showed that the wetlands had the presence of some of the indicative species which categorizes water quality to be slightly polluted to polluted conditions.